The importance of the study of breast neoplasms for the diagnosis: Case report - Kann, Margareth Lima; Barreto, Rafaella Rodrigues; Savelli , Eduardo Vinicius Moreira; Hecke, Lígia Paula Sutille; Medeiros, Suzana Gaspar Lopes de; Ciraudo, Fernanda de Magalhães Lopes; Machado, Heloisa Helena Cardoso; Silva, Gabriella Vasconcelos de Carvalho; Silva, Edson Henrique Oliveira da (Seven Editora, 2024)
Objective: This article aims to highlight the importance of the study of breast neoplasms and their importance for the diagnosis of this disease, regarding its epidemiology, etiology, clinical manifestations, diagnosis, screening and treatment. In addition, to deconstruct the stereotype that all patients with breast cancer present the same manifestations and evolve equally, in addition to reinforcing the understanding that each individual needs comprehensive care, so that not only the doctor, but the entire multidisciplinary team, can provide quality care, observing and respecting the specificities of each person, with the aim of offering - in addition to cancer treatment - quality of life. DOI:https://doi.org/10.56238/sevened2024.001-003